Preventable infant mortality and quality of health care: maternal perception of the child's illness and treatment - Hadad Salime; França Elisabeth; Uchôa Elizabeth (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2002)
This study used a qualitative methodology to analyze the discourse of mothers from Greater Metropolitan Belo Horizonte, Minas Gerais, Brazil, whose infant children had died from what were considered avoidable causes (diarrhea, malnutrition, and pneumonia), seeking to elucidate the factors associated with utilization of health care services. Identification of the illness by the mother was related to perception of specific alterations in the child's state of health. Analysis of the alterations helped identify the principal characteristics ascribed to each alteration and their relationship to the search for treatment. The authors also studied the mother's assessment of treatment received at health care facilities; 43.0% of the cases involved problems related to the structure of health care services or the attending health care professionals. In 46.0% of the cases, mothers associated the child's death with flaws in the health care service. The study group showed a variety of interpretations of illness, often distinct from the corresponding biomedical concepts. The fact that attending health care personnel overlooked or underrated the mother's perception of the illness and the lack of communications between health care personnel and the child's family had an influence on the child's evolution and subsequent death.